BANGKITKAN KESADARAN POLITIKPEMILIH APATIS MELALUI SOSIALISASI ANTI GOLPUT PADA PEMILU DI DESA PEMECUTAN KAJA - Kadek Adyatna Wedananta; Ni Kadek Astri Dewi; Anak Agung Adi Wiryya Putra; Ni Nengah Rupadi Kertiriasih; Putu Suparna (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
The low participation of the community in general elections is often caused by political apathy. Pemecutan Kaja Village is one of the areas that has several reports of abstentions in the election. Therefore, the Community Service Team conducted counseling and socialization activities to increase the political awareness of local residents. The goal is to reduce the abstention rate and increase political participation of the people of Pemecutan Kaja Village in the elections. The activities include counseling on the importance of participating in elections, socialization on voting procedures, open discussions on national and local political issues, and mentoring for first-time voters. As a result, there has been an increase in political understanding and awareness of citizens' voting rights. The hope is that the abstention rate in the elections in Pemecutan Kaja Village will decrease and political participation will increase. This activity is expected to raise political awareness among apathetic voters in Pemecutan Kaja Village